The Influence of Modification of the Surface of Nanoporous Carbon Material by the Oxides of Metals - Rachiy, B.; Nykoliuk, M.; Lisovsky, R.; Kuzyshyn, M.; Merena, R. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
Nitrogen containing carbon materials with metal of oxides (Fe, Ni, Co) prepared by the chemical precipitation method have been shown to be outstanding novel materials for electrochemical capacitors. The electrochemical properties of the electrodes have been studied by considering the effect of the mole ratio of metals. Cyclic voltammetric measurements indicate that nickel, cobalt and iron oxides increase specific capacity of electrochemical capacitors up to 260 F/g in 30% KOH electrolyte. Impedance studies show that the enhanced electrical properties and high frequency response are attributed to the presence of Fe oxides.